'I tell them that sex is sweet at the right time' – A qualitative review of 'pleasure gaps and opportunities' in sexuality education programmes in Ghana and Kenya. Issue 5 (4th May 2021) - Singh, Arushi; Both, Rosalijn; Philpott, Anne
ABSTRACT: Pleasure is a key motivator for sex globally, while unsafe sex is the largest risk factor for young women's mortality and the second for young men. However, framing of sex education and sexual health programmes continues to be around avoiding danger, death and disease, rather than striving for pleasurable, satisfying, and safe sexual experiences. Omission of pleasure and sex-positivity goes against growing evidence that shows that people with more positive views of sexuality are more likely to practice safer sex, use contraception consistently, have higher sexual self-esteem and be more assertive. The Pleasure Project and Rutgers, with GH SRHR Alliance (Ghana) and SRHR Alliance (Kenya), conducted a qualitative pilot study of sexuality education under the Get Up Speak Out programme, analysing the extent to which they included sex-positive content, with recommendations to enhance sex-positivity. Data were collected through interviews with facilitators, focus group discussions with learners, observation of sessions, and curricula content analysis. Findings reveal possibilities of sex-positivity in restrictive contexts, illustrating ways for sexuality education to become more sex-positive and pleasure inclusive. This study enables the development of a new tool for a 'pleasure audit', with markers of high-quality, sex-positive and pleasure-inclusive sexuality education or sexual health programmes.